2013
DOI: 10.1002/meet.14505001051
|View full text |Cite
|
Sign up to set email alerts
|

The role of data reuse in the apprenticeship process

Abstract: The availability of research data through digital repositories has made data reuse a possibility in a growing number of fields. This paper reports on the results of interviews with 27 zoologists, 43 quantitative social scientists and 22 archaeologists. It examines how data reuse contributes to the apprenticeship process and aids students in becoming full members of scholarly disciplines. Specifically, it investigates how data reuse contributes to the processes by which novice researchers join academic communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…Traiano commented that "it [data] has to be preserved somehow," otherwise there is just the report, or as Bradamante noted, it is crucial that "someone really has the duty to see that the digital [data] is stored in a way that it becomes available for, well, perhaps especially to the researchers." Namo criticized the discrepancy between the huge investments in contract archaeology, the enormous research potential of the produced data, and difficulty to access and use it (this critique is not specific to Sweden;e.g., McManus 2012;Faniel et al 2013;Kriesberg et al 2013). In practice, most of the data are hardly used at all after the initial reporting of the fieldwork project.…”
Section: Data As a (Non)boundary Objectmentioning
confidence: 96%
“…Traiano commented that "it [data] has to be preserved somehow," otherwise there is just the report, or as Bradamante noted, it is crucial that "someone really has the duty to see that the digital [data] is stored in a way that it becomes available for, well, perhaps especially to the researchers." Namo criticized the discrepancy between the huge investments in contract archaeology, the enormous research potential of the produced data, and difficulty to access and use it (this critique is not specific to Sweden;e.g., McManus 2012;Faniel et al 2013;Kriesberg et al 2013). In practice, most of the data are hardly used at all after the initial reporting of the fieldwork project.…”
Section: Data As a (Non)boundary Objectmentioning
confidence: 96%
“…Data reuse practices can be distinctive, depending on the types of data being reused, and some research has focused on certain types of data for reuse, such as quantitative (Faniel, Kriesberg, & Yakel, 2016) or qualitative data (e.g., Broom, Cheshire, & Emmison, 2009;Moore, 2007;Yoon, 2014). Several researchers have also conducted multidisciplinary studies, for instance, Birnholtz and Bietz's (2003) research on earthquakes, HIV/AIDS, and space physics, as well as Faniel, Barrera-Gomez, Kriesberg, and Yakel's (2013) investigation of quantitative social science, archaeology, and zoology, through the Dissemination Information Packages for Information Reuse (DIPIR) project from the University of Michigan and OCLC Research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most commonly, previous research has found that data reusers contact data producers (the original investigators of the project in which the data for reuse were created) with questions (Niu, 2009;Yoon, 2016aYoon, , 2017. Sometimes mentors have been involved in locating and understanding data (Kriesberg, Frank, Faniel, & Yakel, 2013;Rolland & Lee, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The literature also suggests that the relevance of data, its understandability and trustworthiness (Thessen & Patterson, ; Zimmerman, ) and perceived data documentation quality (Faniel, Yakel, Kriesberg, & Daniels, ; Niu, , ; Niu & Hedstrom, ) play major roles in scientists’ decisions to reuse available data collected by others. Other studies indicate that there is a difference between how expert and novice scientists perceive and perform data reuse (Faniel et al, ), and underline that training and mentorship are important strategies to support a culture of data reuse (Kriesberg, Frank, Faniel, & Yakel, ). However, a more integrated view of how these factors collectively affect data reuse remains overlooked by previous research.…”
Section: Background and Motivationmentioning
confidence: 99%